International Financial Reporting Standards: history, impact, and new Challenges of the IASB - Ugalde Binda, Nadia (2014)
The internationalization of business transactions, business expansion through mergers and acquisitions, and the interest of covering more diversified investment portfolios, require agencies to draft uniform accounting standards across countries to allow comparability of financial information for these new "multinational companies" (Zeff, 2012). Thus, in 1973 arises the IASC, based in London as a first attempt to establish international basic standards called International Accounting Standards. This article is a historical overview of the institutions involved in the formulation of these rules, the implications that its implementation has had on the financial statements, how some countries have made adjustments to them and what are the main challenges that the IASB should face in the future.